Autoimmunity in monogenic combined immune deficiencies with associated or syndromic features - Sharifinejad, Niusha; Azizi, Gholamreza; Chavoshzadeh, Zahra; Mahdaviani, Seyed Alireza; Alan, Mahnaz Seifi; Tavakol, Marzieh; Sadri, Homa; Nabavi, Mohammad; Ebrahimi, Sareh Sadat; Shirkani, Afshin; Vosughi Motlagh, Ahmad; Safarirad, Molood; et al. (Frontiers in Immunology, 2022)
Background: Combined immune deficiencies (CIDs) with associated or syndromic features are a highly heterogeneous subgroup of inherited immune disorders. These patients represent specific clinical complications with an increased risk of autoimmune conditions. Methods: We analyzed data of monogenic patients with syndromic CIDs adopted from the Iranian inborn errors of immunity registry up to January 2022. A comprehensive comparison in terms of demographic, clinical, and immunological features was performed between patients with and without autoimmunity and also among four mutation groups with the most registered cases including ataxia-telangiectasia mutated (ATM), STAT3 AD (LOF) , DNMT3B/ ZBTB24, and WAS mutations. Results: A total of 137 patients with monogenic syndromic CIDs were included. Most commonly mutated genes were the ATM [80 (58.4%)] and STAT3 AD (LOF) [19 (13.9%)], followed by DNMT3B [11 (8%)], and WAS [11 (8%)]. More than 18% of all patients with syndromic CIDs, including most DNMT3B / ZBTB24 mutations patients, were clinically diagnosed with antibody deficiencies before genetic evaluation. Patients with ATM and WAS mutations had the latest age of onset and the lowest age of diagnosis, respectively. Autoimmune disorders were diagnosed in 24 patients at a median age of 3.5 (2.6-6.0) years, 70.6% of which were diagnosed prior to the diagnosis of immunodeficiency. Lymphoproliferation, particularly hepatosplenomegaly, was significantly higher in patients with autoimmunity (p=0.004). Syndromic CID patients with autoimmunity had significantly lower IgG levels. Hematologic autoimmunity mainly immune thrombocytopenic purpura was the most frequent autoimmunity among major groups of ATM, STAT3 AD (LOF), DNMT3B/ ZBTB24, and WAS mutations, however ATM-mutated patients present more diversified involved organs including rheumatologic, gastrointestinal and dermatologic autoimmunity. Conclusion: About 18% of patients with monogenic syndromic CIDs developed autoimmunity, mainly in the form of hematological immune diseases. Autoimmunity could be an early-onset involvement with a potential diagnostic impact on suspicious cases of syndromic CIDs.